Evaluation of Respiratory Muscle Strength in Mouth Breathers: Clinical Evidences - Andrade da Cunha, Renata; Andrade da Cunha, Daniele; Assis, Roberta Borba; Bezerra, Luciana Ângelo; Justino da Silva, Hilton (International Archives of Otorhinolaryngology, 2014)
Introduction The child who chronically breathes through the mouth may develop a weakness of the respiratory muscles. Researchers and clinical are seeking for methods of instrumental evaluation to gather complementary data to clinical evaluations. With this in mind, it is important to evaluate breathing muscles in the child with Mouth Breathing.Objective To develop a review to investigate studies that used evaluation methods of respiratory muscle strength in mouth breathers.Data Synthesis  The authors were unanimous in relation to manovacuometry method as a way to evaluate respiratory pressures in Mouth Breathing children. Two of them performed with an analog manovacuometer and the other one, digital. The studies were not evaluated with regard to the method efficacy neither the used instruments.Conclusion There are few studies evaluating respiratory muscle strength in Mouth Breathing people through manovacuometry and the low methodological rigor of the analyzed studies hindered a reliable result to support or refuse the use of this technique.
Keywords: Mouth Breathing; muscle strength; evaluation studies